MICROSCOPIC STRUCTURE AND THE PROCESS OF FORMATION OF MILKY SPOTS OF THE GREATER OMENTUM OF WHITE RATS - Hryn, V.H.; Kostylenko, Yu.P.; Maksymenko, O.S.; Tykhonova, O.O.; Tarasenko, Ya.A.; Korchan, N.O. (World of Medicine and Biology, 2023)
To study the microscopic structure and the process of forming milky spots of the greater omentum of white rats, an experimental study was carried out on 15 male white rats of reproductive age, weighing 278.08 to 346.47 grams. The materials were preparations of the greater omentum, fixed in a 10 % neutral formalin solution, as well as total preparations stained with a hematoxylin-eosin solution. Milky spots of the greater omentum of white rats are presented as small lymphoid nodules of various shapes and sizes, which are orderly dispersed within the vascular-fatty arcades on the sides of the axial blood vessels. The smallest were located in the depth of the adipose tissue, adjacent to the axial vessels, and the largest were outside it. Along with them, there were also forms that occupy an intermediate position. All the main types of immunocompetent cells were concentrated in a certain order in the milky spots of the greater omentum.